PENGARUH MODEL BELAJAR DEBAT DALAM MENINGKATKAN KETERAMPILAN BERDISKUSI MAHASISWA STKIP PEMBANGUNAN INDONESIA - Bungatang Bungatang (Cross-border, 2021)
This research is a quasi-experimental research that aims to determine whether there is an influence of the debate learning model on STKIP Pembangunan Indonesia students. The independent variable in this study is the use of the debate learning model, while the dependent variable is the discussion skills of STKIP Pembangunan Indonesia students. The population in this study were all students of STKIP Pembangunan Indonesia, while the samples were class 2C students in the odd semester as an experimental class with 39 students and class 2D students as a control class with 40 students. The research data were obtained by giving a debate test in discussion activities. The data analysis technique is Anacova. Based on the results of the descriptive analysis, the average value of the experimental class was 80.13 and the control class was 70.25 with standard deviations of 8.310 and 9.125, respectively. Based on the results of inferential statistical analysis obtained a significant value of 0.000 < α, then H0 is rejected and H1 is accepted. so it can be concluded that the debate learning model in its application is said to have a significant effect on increasing debating skills in scientific discussion activities of STKIP Pembangunan Indonesia students.